Heat Transfer in a High-pressure Gas-solid Fluidized Bed with Horizontal Tube Bundle and Continuous Addition of Fines - Li, Fang (Université d'Ottawa / University of Ottawa, 2018)
Climate change is becoming more severe than ever in human history and the emission of green house gas urgently needs to be reduced while global energy consumption remains booming. Large-scale application of clean fossil fuel combustion shall be considered as a priority for its economical advantages as well as reliability in meeting global energy needs. Oxygen-fired pressurized fluidized bed combustor technology with downstream carbon capture and sequestration is considered a key approach to clean coal combustion. In such technology, the fluidized bed combustor operates at elevated pressures and houses an in-bed heat exchanger tube bundle. It is essential to understand the rate of heat transfer between the immersed heat exchange surface and the fluidized bed as it is a key parameter in heat exchanger design. The goal of this work was to investigate the impact of pressure and presence of fine particles (i.e., surrogate for pulverized fuel) on the overall tube-to-bed heat transfer coefficient. Experiments were conducted in a pilot-scale fluidized bed with an inner diameter of 0.15 m under cold flow conditions. A tube bundle consisting of five horizontal staggered rows was completely submerged in the bed. One of the tubes was replaced by a heating cartridge housed in a hollowed copper rod. Five thermocouples distributed at 45º intervals along the copper rod circumference measured the surface temperature and ensured that local effects were included. The bed material was large glass beads of 1.0 mm in diameter while the fines were glass beads of 60 µm in diameter and thus susceptible to entrainment. The fine particles were continuously fed to the fluidized bed and then captured downstream by a filter system. Fluidization was conducted at 101, 600 and 1200 kPa with excess gas velocities (Ug - Umf) of 0.21, 0.29 and 0.51 m/s. Fine particle feed rates were 0, 9.5 and 14.4 kg/h. Two heating rod positions (2nd row and 4th row) were studies. Overall, the heat transfer coefficient approximately doubled when pressure was increased from 101 to 1200 kPa. At atmospheric conditions, where the slug flow regime occurred, the maximum heat transfer coefficient was at the bottom of the rod, while it moved to the side of the rod at high pressures where the bubbling regime occurred. As the heating rod moving from 2nd row to the 4th row, the averaged heat transfer coefficient increased by respectively 18%, 9% and 6% at 101, 600 and 1200 kPa. The addition of fine particles decreased the average heat transfer coefficient by 10 to 20 W/m2 K where the time – averaged heat transfer coefficient was approximately 220 and 450 W/m2K at 101 kPa and 1200 kPa respectively. There was no effect on the angular profile across the tube surface. The results showed that average heat transfer coefficients matched the correlation developed by Molerus et al. (1995) within a 5% difference across all conditions when fines were not present.
Keywords: Heat transfer; Horizontal tube bundle; Pressurized fluidized bed